A Comparative Analysis of Marine Water Uses in Italian Coastal Municipalities under the Marine Strategy Framework Directive - Boschetto, R. G.; Capriolo, A.; Mascolo, R. A. (Journal of Environmental Accounting and Management, 2026)
This research addresses an important aspect of the Marine Strategy Framework Directive (MSFD, 2008/56/EC): the analysis of the socio-economic activities that use the marine environment in Italy. To this end, the study focuses on activities related to coastal municipalities as a total contribution of specific economic sectors linked to the sea. A rigorous accounting procedure, in line with the guidelines released by the European Commission’s ESA (Economic and Social Assessment) 2010 Guidance, is provided in order to carry out a meticulous search (data mining) of all the budget items attributable to a reference list of activities and then to follow up with an accounting reclassification capable of describing the largest aggregate of the Sea Economy. The research examines data referred to two different years (2015 and 2019) for three fundamental socio-economic variables: employment, added value and production value. The comparative analysis over time and the spatial distribution dimension enables an in-depth examination of evolving trends and challenges for Italy’s marine environment. A further analysis is performed also to detect the presence of a decoupling effect (when observable) between the socio-economic variables and the trend of some descriptors of the environmental quality. Hence, this research represents not just a significant step towards a complete fulfilling of the MSFD’s requirements, but it also provides valuable insights for future informed policy interventions as well as for the development of sustainable management strategies.